2018
DOI: 10.1007/s10329-017-0648-1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive success of two male morphs in a free-ranging population of Bornean orangutans

Abstract: The reproductive success of male primates is not always associated with dominance status. For example, even though male orangutans exhibit intra-sexual dimorphism and clear dominance relationships exist among males, previous studies have reported that both morphs are able to sire offspring. The present study aimed to compare the reproductive success of two male morphs, and to determine whether unflanged males sired offspring in a free-ranging population of Bornean orangutans, using 12 microsatellite loci to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Kuze et al (2008Kuze et al ( , 2012 reported on the reproductive parameters of female orangutans in Sepilok, comparing them with other sites. Tajima et al (2018) analyzed the reproductive success of a flanged male and an unflanged male.…”
Section: Borneo In 1999mentioning
confidence: 99%
“…Kuze et al (2008Kuze et al ( , 2012 reported on the reproductive parameters of female orangutans in Sepilok, comparing them with other sites. Tajima et al (2018) analyzed the reproductive success of a flanged male and an unflanged male.…”
Section: Borneo In 1999mentioning
confidence: 99%
“…Conversely, unflanged males are generally tolerant of each other and tend to avoid flanged males [5,6]. Flanged males are dominant to unflanged males and displace unflanged males in consortships with females [5,6,[12][13][14]. It has been suggested that flanged males use consortships to mate guard females, as a means to keep other males from mating with a female [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the reproductive success of each morph is essential for testing hypotheses about the evolutionary pressures that resulted in orangutan ARTs. Previous studies of paternity in both Bornean (Pongo pygmaeus) and Sumatran (Pongo abelii) orangutans are limited by incomplete maternity data [40][41][42][43], the inclusion of ex-captive orangutans who may not display natural mating behaviors, or by provisioning from feeding stations and from veterinary care [13,20,44,45] (Table 1). The first orangutan (P. abelli) paternity study found that the two morphs had similar reproductive success and therefore concluded that the two morphs represent alternative mating strategies that coexist as evolutionary stable strategies [20].…”
Section: Introductionmentioning
confidence: 99%
“…Flanged males are dominant over unflanged males and also highly intolerant of each other (Dunkel et al, 2013; Mitani, 1985b; Spillmann, Willems, et al, 2017; Utami Atmoko, Singleton, et al, 2009). Genetic evidence suggests that flanged males achieve most paternities (Banes et al, 2015; Tajima et al, 2018; van Noordwijk et al, in review), whereas unflanged males at least sire some offspring (Goossens et al, 2006; Utami, 2002). Flanged males are preferred by females: receptive, adult females actively approach long calls of dominant, flanged males (Mitra Setia & van Schaik, 2007) and initiate mating with them (Fox, 1998; Knott et al, 2010; O'Connell et al, 2019; Schürmann & van Hooff, 1986).…”
Section: Introductionmentioning
confidence: 99%